The Role of the Housing Market in Workers' Resilience to Job Displacement after Firm Bankruptcy - Jordy Meekes; Wolter Hassink (Institute of Labor Economics (IZA), 2017)
We examine the role of the housing market in workers' adjustment to job displacement. Dutch administrative data were used and analysed with a quasi-experimental design involving job displacement. The empirical design eliminates the potential of endogenous selection into labour turnover. The estimates show that displaced workers experience, in addition to substantial losses in employment and wage, an increase in the commuting distance and a decrease in the probability of moving home. These patterns change over the worker's post-displacement period – the negative displacement effect on wages becomes more pronounced, whereas the increase in the commuting distance diminishes. Also, we examine the role of workers' housing tenure in the displacement effects. Compared with displaced tenants and outright owners, we find that more leveraged displaced owners are more rapidly re-employed and experience a smaller increase in the commuting distance, but experience also a higher loss in wage.
Keywords: J31; J32; J63; J65; R21; R23; 330; commuting distance; geographic mobility; housing tenure; employment; wages